Somatostatin receptors in congenital hyperinsulinism: Biology to bedside - van Albada, Mirjam E.; Mohnike, Klaus; Dunne, Mark J.; Banerjee, Indi; Betz, Stephen F. (Frontiers in Endocrinology, 2022)
Congenital hyperinsulinism (CHI), although a rare disease, is an important cause of severe hypoglycemia in early infancy and childhood, causing preventable morbidity and mortality. Prompt diagnosis and vigorous treatment is necessary to prevent hypoglycaemia mediated brain damage. At present, the medical treatment of CHI is limited to diazoxide as first line and synthetic somatostatin analogs (SSAs) as second line options; therefore understanding somatostatin biology and treatment perspectives is important. Under healthy conditions, somatostatin secreted from pancreatic islet δ-cells reduce insulin release through somatostatin receptor induced cAMP-mediated downregulation and paracrine inhibition of β-cells. Several SSAs with extended durations of action are now available for off-label treatment of CHI. Efficacy remains variable with the present generation of SSAs, with treatment effect often being compromised by loss of initial response and adverse effects such as bowel ischaemia and hepatobiliary dysfunction. In this review we have addressed the biology of the somatostatin system contexualised to CHI. We have discussed the clinical use, limitations, and complications of somatostatin agonists and new and emerging therapies for CHI.